Cloud storage capable to select events upon user request for medium-sized astrophysical experiments. Issue 1 (January 2021) - Kryukov, Alexander; Bychkov, Igor; Korosteleva, Elena; Mikhalov, Andrey; Nguyen, Min-Duc
Abstract: We present a cloud storage for collaborations of small and medium-sized experiments in the field of particle astrophysics. This storage provides a unified interface for accessing data from different experiments. In this article, we will focus on the capabilities of the storage for processing user requests for data, as well as on some technical details of the implementation of data selection. We have deployed a working prototype of the storage. Currently the prototype integrates data from such astrophysical experiments as TAIGA and KASCADE. As a result, users of the respective collaborations have the opportunity to collect scientific data from different experiments seamlessly within one request to conduct joint data analysis.